Ciprofloxacin but not amoxicillin significantly elevated serum peroxynitrite level in patients with enteric (typhoid fever): In vitro study - Al-Nimer, Marwan S.M.; Al-Jrah, Nada A. Abd al-Husain (Journal of the Faculty of Medicine Baghdad, 2006)
Peroxynitrite is one intermediate of reactive nitrogen species with bactericidal and cylotoxic effects. Fluoroquinolones. drugs used for salmonella infections, are interacted v\ith nitrogen species and their baeterieida effect is influenced by these species. This study aims to assess serum peroxynitrite level in patients with enteric (typhoid) fever and. to investigate the effect of ciprofloxacin or amoxicillin on serum peroxynitrite level as well as in aqueous buffer solution in vitro. Thirty patients with enteric fever diagnosed clinically and serologically and twenty healthy individuals served as controls were admitted in this study. None of our sample was received anli-salmonellosis agents. Our results show that serum peroxynitrite level tended to be significantly less in patients with typhoid fever in comparison with controls. In in vitro experimental model, ciprofloxacin but not amoxicillin at 6.25 ug elevate significantly serum peroxynitrite level. In aqueous solution, the ability of ciprofloxacin to produce peroxynitrite is higher than that of amoxicillin. We conclude that Ciprofloxacin . as bactericidal agent against salmonellosis, may act via producing or elevating peroxynitrite level.